Conjoint Analysys Preferences of Milenial or Gen Z in Selecting Online Marketplace Attributes (Adiraku Study Case) - Supardi, Deppy; Napitupulu, Togar Alam (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
In this globalization era, the online marketplace business is a very appealing business. For example, one of the emerging applications is Adiraku. The goal of this study is to determine what attribute preference factors from Millennials or Gen Z influence users in doing online shopping through Adiraku in Jakarta, as well as the contribution of each Adiraku factor. The data analyzed and collected is about Millennials or Gen Z, called The Socializer, and was obtained by means of an online survey focused on Millennials or Gen Z who live in Indonesia. The method used is the conjoint analysis method, which requires quantitative research methods using a descriptive approach to research. Overall, Millennials or Gen Z choose delivery speed as their main preference when using the Adiraku app, which has a vehicle delivery speed of less than 1 day.